1991
DOI: 10.1042/bj2800801
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin-concentration-dependent desensitization of adenylate cyclase in human erythroleukaemia (HEL) cells is abolished by pertussis toxin and enhanced by induction by dimethyl sulphoxide

Abstract: Prostaglandin-regulated cyclic AMP metabolism in human erythroleukaemia (HEL) cells was similar to that previously described in platelets [Ashby (1989) Mol. Pharmacol. 36, 866-873], displaying prostaglandin-concentration-dependent desensitization that could be explained by the presence of separate stimulatory and inhibitory prostaglandin receptors. Pertussis toxin abolished prostaglandin-concentration-dependent desensitization, indicating that the process is mediated through a pertussis toxin-sensitive GTP-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Differentiation with dimethylsulphoxide activates protein kinase C in murine erythroleukaemia cells (Chakraverthy et al, 1992) and accelerates the desensitization rate of G,-coupled prostaglandin E receptors in human erythroleukaemia cells (HEL-cells; Ashby et al, 1991). This differentiation also lowered peak adrenaline-or NPY-stimulated Ca2l elevations, which is compatible with the idea of enhanced desensitization rates for these Gi-mediated responses.…”
Section: Discussionsupporting
confidence: 68%
“…Differentiation with dimethylsulphoxide activates protein kinase C in murine erythroleukaemia cells (Chakraverthy et al, 1992) and accelerates the desensitization rate of G,-coupled prostaglandin E receptors in human erythroleukaemia cells (HEL-cells; Ashby et al, 1991). This differentiation also lowered peak adrenaline-or NPY-stimulated Ca2l elevations, which is compatible with the idea of enhanced desensitization rates for these Gi-mediated responses.…”
Section: Discussionsupporting
confidence: 68%
“…However, several different agonists that stimulate adenylyl cyclase via Gscoupled receptors have been studied in HEL cells and occasionally in other human erythroleukaemia cell lines (Ashby et al 1991;M~ki et al 1992;Feoktistov and Biaggioni 1993). Moreover, the presence of the fl-adrenoceptorcyclase system has been documented repeatedly in erythroid cells of other mammalian species (Beckman et al 1980;Setchenska et al 1983;Sytkowski and Kessler 1984;Moudry and Porzig 1990).…”
Section: Receptor-mediated Effects On Adenylyl Cyclasementioning
confidence: 99%
“…Sequencing reagents were from United States culture flasks in an atmosphere of 95 % air/5 % CO2 at 37 'C. Cells were grown for 4 days in the presence of 1.25 % dimethyl sulphoxide (DMSO) to induce prostaglandin receptors [3]. Sequence comparisons and translations were carried out using the GCG Sequence Analysis Package (University of Wisconsin).…”
Section: Kb Longmentioning
confidence: 99%
“…We have suggested that prostaglandin regulation of cyclic AMP metabolism in platelets involves separate stimulatory and inhibitory prostaglandin receptors linked to adenylate cyclase, giving rise to characteristic patterns of cyclic AMP formation that may buffer the cellular response to localized changes in prostaglandin concentration [1,2]. We have shown similar regulation of cyclic AMP metabolism in human erythroleukaemia (HEL) cells [3], a megakaryocytic cell line possessing several platelet-like features [4] that has been used for cloning of platelet-specific receptors such as the thrombin receptor [5].…”
Section: Introductionmentioning
confidence: 98%